2016
DOI: 10.1007/s00125-016-4192-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of intestinal microbiota and microbial metabolites in metabolic control

Abstract: The role of the intestinal microbiota and microbial metabolites in the maintenance of host health and development of metabolic disease has gained significant attention over the past decade. Mechanistic insight revealing causality, however, is scarce. Work by Ussar and co-workers demonstrates that a complex interaction between microbiota, host genetics and environmental factors is involved in metabolic disease development in mice. In addition, Perry and coworkers show that the microbial metabolite acetate augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Diabetes and obesity are lifestyle-related disorders that could cause an increased incidence of gut dysbiosis [29], which is directly related to alterations in gut microbial-related metabolites [30].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and obesity are lifestyle-related disorders that could cause an increased incidence of gut dysbiosis [29], which is directly related to alterations in gut microbial-related metabolites [30].…”
Section: Discussionmentioning
confidence: 99%
“…SCFA production is generally associated with health when produced in the gut by colonic bacteria, typically through fermentation of dietary fiber. Specific metabolites such as butyrate, when provided in a dietary supplement, have shown beneficial health effects in the host (van Immerseel et al, 2010;Herrema et al, 2017). In contrast, butyrate production in the oral cavity is reported to be cytotoxic in patients with oral disease, such as periodontal infection, and has been shown to be responsible for the release of reactive oxygen species in chronic periodontitis (Anand et al, 2016).…”
Section: Insights and Limitations Of The Predicted Morphological Clasmentioning
confidence: 99%
“…Obesity (body-mass index ³30kg/m 2 ) is the result of long-term energy homeostasis imbalance (e.g increased food intake, decreased energy expenditure) involving brain and peripheral organs (1). Obesity is the cause of many complications, including diabetes, liver diseases, cardiovascular diseases or even neurological dysfunction such as memory dysfunction or pain (2,3) Recently, the gut microbiome and its derivative metabolites have received attention as potential causes and/or consequences of obesity (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A seminal work by Backhed et al showed that germ-free mice are protected from developing diet-induced obesity, demonstrating the crucial role played by gut microbiome in energy balance, substrate utilization and glucose homeostasis (15).…”
Section: Introductionmentioning
confidence: 99%